Flood Hazard Mapping via High-Resolution Imagery - Rohman, Arif; Nuha, Muhammad Ulin; Wibowo, Yudha Gusti; Sigalingging, Roy Chandra P.; Jumadi, Jumadi; Zamzami, Hamza Ait; Ibrahim, Mohd Hairy (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Urban flooding in low-lying coastal zones like Way Lunik, Bandar Lampung, presents a growing challenge driven by rapid land use change, degraded infrastructure, and limited hydrological planning. This study combines high-resolution UAV-derived Digital Surface Models (DSM), national elevation data (DEMNAS), satellite imagery, and field-based drainage surveys to analyze flood risk in the Way Lunik watershed. Hydrological modeling shows that the watershed acts as a terminal catchment with low slopes and only two main discharge points, making it prone to runoff accumulation and tidal backflow. Significant mismatches between modeled and observed drainage patterns stem from blocked channels, informal settlements, and outdated infrastructure. Land cover analysis (2017–2023) reveals substantial growth in impervious surfaces, especially over former green or agricultural areas, increasing runoff and decreasing infiltration. Field surveys confirm drainage blind spots, unplanned flow paths, and encroached outlets in industrial and residential zones. The study also maps building types and clusters of flood-prone areas, often overlapping with marginalized neighborhoods and public facilities. By integrating elevation data, UAV imagery, and ground mapping, this research provides a spatially detailed assessment of urban flood hazards, emphasizing the importance of watershed-scale planning, infrastructure renewal, and the role of UAVs in adaptive flood risk management.